2020
DOI: 10.1039/c9cc08671d
|View full text |Cite
|
Sign up to set email alerts
|

Monomer-targeting affinity peptide inhibitors of amyloid with no self-fibrillation and low cytotoxicity

Abstract: A monomer-targeting strategy based on solution-phase biopanning to obtain peptide inhibitors increases the suppression efficiency and reduces the cytotoxicity of amylin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The absence of β‐sheet structures in the conformational ensemble of the hIAPP‐ANFLVH complex is consistent with circular dichroism (CD) results, which highlighted the prevention of the formation of β‐sheet in hIAPP on the addition of ANFLVH peptide at equimolar or higher concentrations [39] . The results of the secondary structure analysis are consistent with Xuan et al., which reported that LA12 (LTPHKHHKHLHA) stabilized hIAPP in a random coil conformation, which, in turn, prevented the conformational transition to aggregation‐prone β‐sheet conformation and formation of hIAPP fibrils [38] . Further, Lao et al.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The absence of β‐sheet structures in the conformational ensemble of the hIAPP‐ANFLVH complex is consistent with circular dichroism (CD) results, which highlighted the prevention of the formation of β‐sheet in hIAPP on the addition of ANFLVH peptide at equimolar or higher concentrations [39] . The results of the secondary structure analysis are consistent with Xuan et al., which reported that LA12 (LTPHKHHKHLHA) stabilized hIAPP in a random coil conformation, which, in turn, prevented the conformational transition to aggregation‐prone β‐sheet conformation and formation of hIAPP fibrils [38] . Further, Lao et al.…”
Section: Resultssupporting
confidence: 89%
“…[39] The results of the secondary structure analysis are consistent with Xuan et al, which reported that LA12 (LTPHKHHKHLHA) stabilized hIAPP in a random coil conformation, which, in turn, prevented the conformational transition to aggregation-prone β-sheet conformation and formation of hIAPP fibrils. [38] Further, Lao et al also highlighted the prevention of the formation of βsheet conformation by hIAPP dimer in the presence of dopamine by employing replica-exchange MD simulations. [53] Dopamine displayed preferential binding with Arg11, Leu12, Phe15, His18, Phe23, Ile26, Leu27, and Tyr37 residues of hIAPP and prevented the β-sheets formation in the amyloidogenic regions of hIAPP.…”
Section: Secondary Structure Analysis Of Hiapp and Hiapp-anflvh Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…9,[11][12][13] Until now, a stream of strategies have been applied to prevent and suppress the IAPP self-assembly process. [14][15][16][17][18][19][20][21] However, most amyloidogenesis inhibitors developed based on these endeavors are effective only at molar excess, mainly because of the lack of high binding affinity or specificity.…”
Section: Introductionmentioning
confidence: 99%